Biosynthesis of silver nanoparticles using cananga odorata (lam.) Hook.f. & thomson. Stem broth – an eco-friendly Approach (Funded Work) - N.I. HULKOTI; T.C. TARANATH (International Journal of Pharma and Bio Sciences, 2018)
Medicinal plants, due to over utilization for their profound scientific attentiveness are at the verge of extinction and many of them already extinct. The current investigation epitomizes the phytofabrication of silver nanoparticles of miscellaneous dimensions, using Cananga odorata (Lam.) Hook.f. &Thomson. stem broth, the plant with meagre medicinal cognisance. The formulated nanoparticles were employed to assess anti-bacterial proficiency. Physico-chemical parameters viz. contact time, stem broth quantity, pH, temperature, and silver nitrate concentration were evaluated and assessed to fabricate nanoparticles of nanoscopic sizes. The nanoparticles were characterized by UV–vis spectroscopy, FT-IR spectroscopy, EDS, XRD, HRTEM. The outcome confirms, the nanoparticles were crystalline, negatively charged, stable, and spherical shaped. The nanoparticles accordingly engineered were evaluated against bacteria Staphylococcus aureus MTCC 3160 (gram positive bacteria) and Salmonella typhi MTCC 3216 (gram negative bacteria) for antibacterial intensity. The nanoparticles developed, exhibited anti-bacterial activity only in two physico-chemical parameters viz. stem broth quantity and temperature whereas contact time, pH and silver salt concentration did not show any anti-microbial action. Cananga odorata stem broth did not show any antibacterial efficacy. Cananga odorata is a plant with passable medicinal prominence. Its antimicrobial property came to light by employing the synthesized silver nanoparticles to test anti-microbial activity. This research plans for a certain possibility to use non-medicinal plants, and fabricate antimicrobial nanoparticles from them through nanotechnology as they exhibit a substantial prospective in pharmaceutical industry.